A. \(\mathop {\max }\limits_{\left[ {1;3} \right]} f(x) = - 6.\)
B. \(\mathop {\max }\limits_{\left[ {1;3} \right]} f(x) = \frac{{13}}{{27}}.\)
C. \(\mathop {\max }\limits_{\left[ {1;3} \right]} f(x) = 0.\)
D. \(\mathop {\max }\limits_{\left[ {1;3} \right]} f(x) = 5.\)
B
Ta có \(f'(x) = 3{x^2} - 16x + 16\)
\(f'(x) = 0 \Leftrightarrow 3{x^2} - 16x + 16 = 0 \Leftrightarrow \left[ \begin{array}{l}x = 4 \notin \left[ {1;3} \right]\\x = \frac{4}{3} \in \left[ {1;3} \right]\end{array} \right.\)
\(f(1) = 0;\,f\left( {\frac{4}{3}} \right) = \frac{{13}}{{27}};\,f(3) = - 6.\)
Vậy \(\mathop {\max }\limits_{{\rm{[}}1;3]} f(x) = \frac{{13}}{{27}}.\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247